STUDI PENDAHULUAN DAERAH PENYEBARAN, POPULASI, DAN HABITAT BETET JAWA - W. Widodo (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2007)
On April and September 2006, preliminary study to know the distribution, population status and habitat of the Javan moustached parakeets (Psittacula alexandri alexandri Linnaeus 1758) were conducted in the Baluran and Alas Purwo National Parks (East Java) and in the Tilu Geder Mountain Forests and in the Darmaga IPB Campus Parks (West Java). Direct and indirect observations were used in this research. The results are found only 2 individuals of birds in the Darmaga IPB Campus Parks. However, 45 species of plants were recorded as the natural food resources for the Javan moustached parakeets in the fields. Almost 60% parts of plants i.e., fruits were food by birds, even if those birds are more frugivorous. Some species of plants were known as the nesting trees for the species, namely: Tectona grandis, Acacia lecophloea, Azadirachta indica, Tetrameles nudiflora and Eucalyptus deglupta. The Javan moustached parakeets have needed mangrove forests, beach forests, evergreen forests and old teak forests for their activities. The population and their habitat of javan parakeets are threatened by forest fragmentation effects and over hunting.